Exploring the Types of GBV Reported in Kibera Slums and the Available Interventions - Wairimu, Wanjohi B.; Keraka, Margaret; Mutabazi, Michel (My University, 2023)
Worldwide, gender-based violence (GBV) is quite prevalent with domestic violence being voiced as the most common (WHO, 2020). The WHO states that about 35% of women in the world have had an experience once in a lifetime of either sexual and/or physical non-partner or intimate partner sexual violence (WHO, 2020). Gender-based violence is the most widespread, socially tolerated human rights violation in the world. It kills; disables and harms more people especially women. The violence can take many forms including physical, sexual, psychological, and economic violence (WHO, 2020). In Kenya, about 45% of women aged 15 - 49 years reported having experienced various forms of gender-based violence in their lifetime, and out of these, 29% women reported having had the experience in the previous year. Besides, 16% women had experienced sexual abuse in their lifetime, and 13% of the women had it in the previous year (KDHS, 2014). Kibera slums is one of the biggest informal settlements in Kenya and largest slum in Sub-Saharan Africa where various issues have been reported including insecurity, poor water, hygiene and sanitation, poor housing among others. Majority of its inhabitants are of very low socio economic status. The purpose of this study was to explore the types of GBV prevalent in Kibera slums and the available interventions to address this problem. This study specific objectives were to identify the types of GBV reported by women of reproductive age in Kibera slums and to find out the types of GBV interventions offered to women of reproductive age in Kibera. The study adopted a cross-sectional study design. This used a mixed methods research where both qualitative and quantitative data were collected using a questionnaire and analyzed. The study respected the ethical considerations in research. The results showed that women of reproductive age in Kibera slums had experienced many forms of gender-based violence. Out the 390 respondents, 34 (8.7%) had experienced physical abuse, 95 (24.4%) had experienced verbal abuse and 60(15.4%) experienced sexual harassment while 91 (23.3%) of the respondents had not experienced any type of GBV. Most survivors 147 (49.1%) of GBV had never received any interventions. Only 39 (13.1%) of the survivors of GBV had received medical treatment, 44 (14.7%) had received guidance and counselling and incorporated to a support group, only 13 (4.3%) had taken legal measures against the perpetrators. In Kibera slums, all forms of gender-based violence are still prevalent and more interventions are needed to address this public health issue with a special focus on informal settlements.
Keywords: Kibera slums; women of reproductive age; gender-based violence; interventions